Taxes and Public Spending in Indonesia : Who Pays and Who Benefits? - Indonesia Ministry of Finance; World Bank (World Bank, Jakarta, 2016)
Inequality in Indonesia is rising rapidly. During the 1997-98 Asian financial crisis, poverty rosesharply, while the Gini measure of inequality fell, as the richest were the hardest hit. Since then, the Gini has increased from 30 points in 2000 to 41 points in 2014, its highest recorded level. In 2002, the richest 10 percent of Indonesians consumed as much as the poorest 42 percent combined; by 2014, they consumed as much as the poorest 54 percent. Even this is likely to be understated, as household surveys often miss the rich. Indonesias level of inequality is now becoming high and climbing faster than most of its East Asian neighbors.